2018
DOI: 10.1055/a-0735-9911
|View full text |Cite
|
Sign up to set email alerts
|

Serine Protease Mauritanicain from Euphorbia mauritanica and Phorbol-12-myristate-13-acetate Modulate the IL-8 Release in Fibroblasts and HaCaT Keratinocytes

Abstract: In recent years, skin reactions such as phytophotodermatitis, contact dermatitis, and other inflammatory responses after contact with chemicals from various plants, e.g., Heracleum mantegazzianum or Hippomane mancinella, are one of the hot topics in phytobiology. Occupational skin inflammation after contact with latices of plants from Euphorbiaceae are common among people who work with plants of this family. Activation of protein kinase C by G protein-coupled receptors such as protease-activated receptors is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…The plant was reported to induce antiproliferative activities in lung cancer cells and has an anti-inflammatory effect on primary human dermal fibroblasts. 17 The findings of our study recorded the antiviral activity of this plant for the first time. E. trigona has remarkable anti-swarming properties against Proteus mirabilis and Pseudomonas aeruginosa.…”
Section: Discussionmentioning
confidence: 63%
“…The plant was reported to induce antiproliferative activities in lung cancer cells and has an anti-inflammatory effect on primary human dermal fibroblasts. 17 The findings of our study recorded the antiviral activity of this plant for the first time. E. trigona has remarkable anti-swarming properties against Proteus mirabilis and Pseudomonas aeruginosa.…”
Section: Discussionmentioning
confidence: 63%
“…The clinical symptoms are erythema and eczema formation. Regarding the mechanism underlying the inflammatory response to lattices of plants from the Euphorbiaceae family, a recent study showed that the serine protease mauritanicain and phorbol-12-myristate-13-acetate (PMA) modulate the release of the pro-inflammatory cytokine IL-8 in fibroblasts and the human keratinocyte cell line HaCaT in a protease activated receptor-dependent manner after in vitro stimulation for 60 min [27]. This study is in line with a previous work by Domsalla and Melzig, who showed that a combination of proteases and PMA promotes inflammatory responses in the human monocyte-like cell line U937 [28].…”
Section: Recent Recommendations Regarding Testing For Plant Contact Dmentioning
confidence: 99%
“…In Bezug auf den Mechanismus, welcher der entzündlichen Reaktion auf Milchsaft von Pflanzen aus der Euphorbiaceae-Familie zugrunde liegt, hat eine kürzlich veröffentlichte Studie gezeigt, dass die Serinprotease Mauritanicain sowie Phorbol-12-Myristat-13-Acetat die Freisetzung des pro-inflammatorischen Zytokins IL-8 modulieren. Dies geschieht sowohl in Fibroblasten als auch der humanen Keratinozyten-Zelllinie HaCaT auf Proteaseaktivierte Rezeptor (PAR)-abhängige Weise nach In-vitro-Stimulation der Zellen für 60 Minuten [18]. Diese Studie steht im Einklang mit einer früheren Arbeit von Domsalla und Melzig, die zeigten, dass eine Kombination von Proteasen und PMA Entzündungsreaktionen in der humanen Monozyten-ähnlichen Zelllinie U937 fördert [19].…”
Section: Jüngste Fortschritte Beim Verständnis Der Immunologischen Meunclassified